Enhancer turnover and conserved regulatory function in vertebrate evolution - Domene, Sabina (2013)
Mutations in regulatory regions including enhancers are an important source of variation and innovation during evolution. Enhancers can evolve by changes in the sequence, arrangement and repertoire of transcription factor binding sites, but whole enhancers can also be lost or gained in certain lineages in a process of turnover. The proopiomelanocortin gene (Pomc), which encodes a prohormone, is expressed in the pituitary and hypothalamus of all jawed vertebrates. We have previously described that hypothalamic Pomc expression in mammals is controlled by two enhancers?nPE1 and nPE2?that are derived from transposable elements and that presumably replaced the ancestral neuronal Pomc regulatory regions. Here, we show that nPE1 and nPE2, even though they are mammalian novelties with no homologous counterpart in other vertebrates, nevertheless can drive gene expression specifically to POMC neurons in the hypothalamus of larval and adult transgenic zebrafish. This indicates that when neuronal Pomc enhancers originated de novo during early mammalian evolution, the newly created cis- and trans-codes were similar to the ancestral ones. We also identify the neuronal regulatory region of zebrafish pomca and confirm that it is not homologous to the mammalian enhancers. Our work sheds light on the process of gene regulatory evolution by showing how a locus can undergo enhancer turnover and nevertheless maintain the ancestral transcriptional output.